Comprehensive assessment of pesticide use patterns and increased cancer risk - Gerken, Jacob; Vincent, Gear Thomas; Zapata, Demi; Barron, Ileana G.; Zapata, Isain (Frontiers in Cancer Control and Society, 2024)
Pesticides are an essential feature of modern-day agriculture that adds to the list of factors that increase cancer risk. Our study aims to comprehensively evaluate this relationship through a population-based approach that considers confounding variables such as county-specific rates of smoking, socioeconomic vulnerability, and agricultural land. We achieved our goal with the implementation of latent-class pesticide use patterns, which were further modeled among covariates to evaluate their associations with cancer risk. Our findings demonstrated an association between pesticide use and increased incidence of leukemia; non-Hodgkin's lymphoma; bladder, colon, lung, and pancreatic cancer; and all cancers combined that are comparable to smoking for some cancer types. Through our comprehensive analysis and unique approach, our study emphasizes the importance of a holistic assessment of the risks of pesticide use for communities, which may be used to impact future policies regarding pesticides.